GE_GERICHTE P/9020/2018 vom 24. Juni 2020 - GE Cour de justice (2020)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT;CONTRAINTE SEXUELLE;VIOL;SEQUESTRATION;FIXATION DE LA PEINE | CP.187.ch1; CP.189; CP.190.al1; CP.183.ch1